ARID1A Deficiency Impairs the DNA Damage Checkpoint and Sensitizes Cells to PARP Inhibitors - Shen, Jianfeng (Cancer Discov, 2015)
ARID1A, a chromatin remodeler of the SWI/SNF family, is a recently identified tumor suppressor that is mutated in a broad spectrum of human cancers. Thus, it is of fundamental clinical importance to understand its molecular functions and determine whether ARID1A deficiency can be exploited therapeutically. In this manuscript, we report a key function of ARID1A in regulating the DNA damage checkpoint. ARID1A is recruited to DNA double strand breaks (DSBs) via its interaction with the upstream DNA damage checkpoint kinase ATR. At the molecular level, ARID1A facilitates efficient processing of DSB to single strand ends, and sustains DNA damage signaling. Importantly, ARID1A deficiency sensitizes cancer cells to PARP inhibitors in vitro and in vivo providing a potential therapeutic strategy for patients with ARID1A-mutant tumors.